200 contractual problems and their solutions - Knowles, Roger (Oxford : Wiley-Blackwell, 2012)
This book examines 200 contractual problems which regularly arise on building and engineering projects and provides a detailed explanation of their solutions, citing standard contract conditions and key parts of legal judgements as authority. A succinct summary is provided at the end of each detailed solution.
Includes bibliographical references and index.
oif 16/12/2019
Loans
Keywords: Contracts